Concealed carry - Andrews, Spencer; Colacito, Riccardo; Croce, Mariano M.; Gavazzoni, Federico (Journal of Financial Economics, 2024)
The slope carry takes a long (short) position in the long-term bonds of countries with steeper (flatter) yield curves. The traditional carry takes a long (short) position in countries with high (low) short-term rates. We document that: (i) the slope carry return is slightly negative (strongly positive) in the pre (post) 2008 period, whereas it is concealed over longer samples; (ii) the traditional carry return is lower post-2008; and (iii) expected global growth and inflation declined post-2008. We connect these findings through an equilibrium model in which countries feature heterogeneous exposure to news shocks about global output and global inflation .